(untitled) (Journal of the College of Basic Education, 2024)
In their current research, the two researchers tried to identify the most important strategies that emerged from the theory of cognitive burden, from which the strategy of the solution was chosen and completed the issue, and after the theory, its principles and characteristics were presented, and the most important strategies that started from this theory, were built according to the theory applications, and after it was done Displaying six strategies The researchers touched on the strategy of the solution example and completing the issue, and explaining its most important steps and teaching stages, and after that it touched on the importance of using this strategy in teaching students in the primary stage, as it keeps pace with their mental levels and their knowledge experiences, and it increases their levels of cognitive achievement in the event that they are used in teaching Various subjects, especially Arabic language subjects and Arabic grammar, in particular. The two researchers touched on the most important classifications that dealt with questions, examples and exercises because of their close association with the steps of this strategy, and then there were some recommendations and proposals for their use in teaching students in the primary stage in Iraqi schools.